PENGARUH DIGITAL MARKETING DAN STRATEGI PROMOSI TERHADAP EFEKTIVITAS PENJUALAN JASA DI LPP RRI MADIUN - Rifky Avivah Husnul Khuluq; Elliv Hidayatul Lailiyah (PT Naureen Digital Education, 2026)
This study aims to determine and analyze the influence of digital marketing and promotional strategies on the effectiveness of service sales at LPP RRI Madiun. The research employed a quantitative method with a deductive approach. The population consisted of 300 users of LPP RRI Madiun broadcasting services during the period of January–April 2026. A sample of 75 respondents was selected using the Slovin formula and simple random sampling technique. Data were collected through questionnaires utilizing a Likert scale. Data analysis was conducted using multiple linear regression with the assistance of IBM SPSS version 26. The results indicate that digital marketing has a positive and significant effect on service sales effectiveness. Promotional strategies also have a positive and significant effect on service sales effectiveness. Simultaneously, digital marketing and promotional strategies have a positive and significant effect on service sales effectiveness at LPP RRI Madiun. The coefficient of determination test shows an R Square value of 0.527, indicating that digital marketing and promotional strategies explain 52.7% of the variance in service sales effectiveness, while the remaining 47.3% is influenced by other factors outside the research model. The findings suggest that better implementation of digital marketing and promotional strategies leads to increased effectiveness of service sales.